Dynamics of disordered Rydberg lattice gases with constraints - Ostmann, Maike (2020)
Recent advances in the manipulation of cold atoms within a tailored optical tweezer array allow for the production of Rydberg quantum simulators. In this thesis we analyze disordered and constrained many-body dynamics by utilizing such a system. Using a one-dimensional quantum simulator platform, we employ single-site addressing to analyze three distinct protocols based on the Rydberg blockade mechanism. These protocols allow for the preparation of an antiferromagnetic GHZ state and a matrix product state, as well as the transport of a quantum state.